2023
DOI: 10.1088/1748-0221/18/04/p04026
|View full text |Cite
|
Sign up to set email alerts
|

OPTIma: a tracking solution for proton computed tomography in high proton flux environments

Abstract: Currently there is a large discrepancy between the currents that are used for treatments in proton beam therapy facilities and the ultra low beam currents required for many proton CT imaging systems. Here we provide details of the OPTIma silicon strip based tracking system, which has been designed for performing proton CT imaging in conditions closer to the high proton flux environments of modern spot scanning treatment facilities. Details on the physical design, sensor testing, modelling, and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…The resulting performance in terms of RSP discrepancy as a function of beam current is shown in figure 11. As was seen in earlier studies using a resolving calorimeter (Winter et al 2023), the overall trends are that the RSP discrepancy gets larger with (i) beam current and (ii) as the contrast with the surrounding material gets larger. This is largely due to failures in the track reconstruction, where as the number of hits in the system increases, so too does the chance of incorrectly matching hits across modules.…”
Section: Full Detector Modelsupporting
confidence: 66%
See 2 more Smart Citations
“…The resulting performance in terms of RSP discrepancy as a function of beam current is shown in figure 11. As was seen in earlier studies using a resolving calorimeter (Winter et al 2023), the overall trends are that the RSP discrepancy gets larger with (i) beam current and (ii) as the contrast with the surrounding material gets larger. This is largely due to failures in the track reconstruction, where as the number of hits in the system increases, so too does the chance of incorrectly matching hits across modules.…”
Section: Full Detector Modelsupporting
confidence: 66%
“…A detailed description of the OPTIma tracking system has already been presented (Winter et al 2023), and it has been shown that with a suitable calorimeter, the tracking system could facilitate a discrepancy of less than 1% on the measured RSP of various tissues for beam currents up to 50 pA at the nozzle at the Christie research line.…”
Section: Trackingmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the tracker lateral dimensions are only about 10 cm, so the prototype is limited to making CT images of phantoms much smaller than, for example, a human head. It does nevertheless illustrate the technological principle, and the collaboration is currently working on building an advanced, well funded, full-scale system named OPTIma (Winter et al 2023).…”
Section: Range Detectorsmentioning
confidence: 99%
“…The Bergen collaboration is working on an instrument that could be the ultimate pCT scanner in terms of speed and RSP resolution and is inherently capable of measuring many simultaneous particles. The PRaVDA/OPTIma project is funded and well underway, with tracking based on silicon strip sensors and a segmented energy detector that is not yet well defined but may be based on scintillating bars (Winter et al 2023). It is aiming for advanced performance that would be useful in a clinical setting, in particular a capability to handle high rates in a scanned pencil beam, with up to seven charged-particle tracks measured simultaneously.…”
Section: Outlook and Conclusionmentioning
confidence: 99%